A High Seebeck Voltage Thermoelectric Module with P‐type and N‐type MAPbI3 Perovskite Single Crystals. (22nd January 2021) - Xie, Zuoxiang; Feng, Kai; Xiong, Yan; Chen, Xu; Liang, Yudong; Abid, Kamran; Xu, Ling
Abstract: In recent years, organic–inorganic hybrid halide perovskite materials have been found to have low thermal conductivity and a large Seebeck effect, giving them great potential for thermoelectric applications. More stable single crystals make this possible. In this work, high‐quality MAPbI3 single crystals are prepared using a modified solvent engineering method, and their trap density is as low as 2.5 × 10 9 cm −3 . It is noticed that the reaction between the crystal a metal electrode causes different degrees of doping effect along the vertical direction, leading to an increase in the intrinsic P‐type with Au metal, and forming N‐type semiconductor characteristics with Ag metal. A high Seebeck voltage thermoelectric module is obtained by combining the perovskite single crystal with different conductive characteristics. After device optimization, the thermoelectric potential of the champion module reaches a high voltage of 337 mV at 115 °C, the maximum output power with load reaches about 30 nW, and the theoretical maximum power reaches 65 nW. It is hoped that this research can promote the development of low thermal conductivity perovskite materials in the thermoelectric field. Abstract : It is noted that an Au layer will enhance the intrinsic P‐type conductivity of an MAPbI3 single crystal, while an Ag layer changes the intrinsic P‐type conductivity to N‐type. Novel P‐type and N‐type perovskite crystals are combined to form a thermoelectric module device with a theoretical output power of 64.5673 nW.